Academics' diversification enhancing graduate employability through the scholarship of teaching and learning / Faizah A. Majid - A. Majid, Faizah (Universiti Teknologi MARA, 2016)
Current debates on higher education graduates seem to address graduates’ quality and their employability. Since industries’ role as future employers become central in the preparation of graduates, issues on graduate employability (GE) have become one of the heated discussion topics with the inclusion of smart partnerships and collaborations between higher education institutes and industries. As students generally spend between three and five years in higher education institutes prior to graduating, students’ graduate employability relies quite heavily on the preparation for the world of work during their time in the institutions. The Ministry of Higher Education has called for academics to collaborate with the industries as a measure to enhance GE. Needless to say, academics’ diversification has always directed them to be multi-taskers. Four main professional tracks inevitable amongst the academics namely; teaching, research (and publication), community service and academic leadership have made the academic profession a diversed one. While this is easy to comprehend, the task to establish and maintain linkages with industries in enhancing GE remains an issue yet to be championed by the academics who are already swamped by various academic tasks, let alone collaborating with the industries to specifically promote graduate employability. This paper examines the issues of graduate employability alongside the diversed tasks of the academics. Based on Boyer’s scholarship of teaching and learning (SOTL), this paper aims to address how GE could be enhanced amidst the academics’ diversification. The proposed framework is hoped to pave the way forward for the academics to play their parts in enhancing GE amidst their diversification in order to achieve the Ministry of Higher Education aspiration of ‘soaring upwards’.